A study on the popularity of k-pop among teenagers in Malaysia - Soo, Yee Jean (2023)
With the popularization of YouTube, a well-standardized training system, powerful visual effects, good music quality, and the message they are trying to send that is resonance with the audience, K-POP has become a global phenomenon and is liked by people all around the world. The purpose of this study is to investigate why K-Pop is so popular among Malaysian teenagers and to investigate the level of K-Pop addiction among Malaysian teenagers. Research on the topic will be conducted using quantitative methods. The platform of choice for creating online survey forms and receiving most of the focus group data will be Google Forms. To reach the 100 respondents, the 100 online survey forms will be distributed along with a link on various social media channels. Statistical Package for the Social Sciences (SPSS) will be used to analyse the data after it has been obtained.